Composite anti-displacement asphalt concrete structure and construction method thereof
By using a high-pore skeleton structure to grout and fill gelling agent and laying modified asphalt wear layer in asphalt concrete pavement, the problem of relocation of traditional asphalt pavement under high shear stress is solved, and the high strength of the pavement is achieved , anti-deformation and anti-slip properties extend the service life of the road surface.
Patent Information
- Application Number
- CN202411402229.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-14
AI Technical Summary
When traditional asphalt pavement faces high shear stress and continuous horizontal forces, it is difficult to resist the stress caused by road transportation, resulting in road surface displacement, packing, rut and other diseases. Repeated milling and reworking increases maintenance costs and damages the pavement structure.
The composite anti-push asphalt concrete structure is adopted, and the anti-slip performance of the pavement is enhanced by grouting and filling gelling agent in the high-pore frame structure, and a modified asphalt wear layer is added to improve the anti-slip performance of the pavement.
It has achieved high skeleton strength, early strength, water stability, and good resistance to deformation and ruts on the road surface. At the same time, it has improved the anti-slip performance of the road surface and extended the service life of the road surface.
Smart Images

Figure CN119434048A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road maintenance, and in particular relates to a composite anti-displacement asphalt concrete structure and a construction method thereof. Background Art
[0002] With the rapid development of domestic highway transportation, the characteristics of heavy axle load, large flow and channelized traffic in road transportation are becoming more and more prominent. At the intersections of national and provincial highways, municipal roads and long longitudinal slopes of highways of all grades, due to frequent braking and starting of cars, passing vehicles impose high shear stress and continuous horizontal force on traditional asphalt concrete pavement. When the high driving shear stress is greater than the shear stress of the asphalt concrete structure, the continuous accumulation of flow deformation will form pavement displacement, bumps, rutting and other diseases. Such diseases will eventually develop into serious structural diseases such as spalling, potholes, water damage, etc., which are particularly obvious at special sections such as road intersections and long longitudinal slopes.
[0003] Although traditional asphalt pavement milling and repaving can suppress the development of diseases caused by flow deformation in a short period of time, the shear stress of the newly paved pavement is always insufficient to resist the high shear stress and continuous horizontal force caused by road transportation. The occurrence of flow deformation is not fundamentally solved, resulting in repeated milling and repair of the road, resulting in an increase in maintenance costs. Multiple repairs can also easily cause structural damage to the asphalt pavement, thereby reducing the service life of the road surface. Summary of the invention
[0004] In view of the difficulty of the traditional asphalt pavement milling and re-paving construction process to resist the high shear stress and continuous horizontal force caused by road transportation at national and provincial roads, municipal road intersections and long longitudinal slopes of various grades of highways, and the problem that repeated milling and repairing cause increased maintenance costs and structural damage to the asphalt pavement, the present invention provides a composite anti-displacement asphalt concrete structure and its construction method. The composite anti-displacement asphalt concrete structure provided by the present invention adopts a grouting process to fill the gaps between the skeletons on the basis of the gradation of the high-porosity skeleton structure, and then a modified asphalt wear layer is added. The formed pavement has high skeleton strength, early strength, water stability, good deformation resistance and rutting resistance, and at the same time has excellent road surface anti-skid performance, and has high application value.
[0005] The technical solution adopted by the present invention is as follows:
[0006] 1. A composite anti-slip asphalt concrete structure
[0007] The composite anti-slip asphalt concrete structure includes a modified emulsified asphalt tack coat, an asphalt concrete middle surface layer, a filling gelling agent and a modified asphalt wear layer; the asphalt concrete middle surface layer is spread on the surface of the modified emulsified asphalt tack coat, the filling gelling agent is formed inside the asphalt concrete middle surface layer by a grouting process, and the modified asphalt wear layer is formed on the surface of the asphalt concrete middle surface layer by a paving process.
[0008] The asphalt concrete middle surface layer comprises the following raw materials in parts by weight: 100 parts of mineral material I, 0.1-0.11 parts of fiber and 4.5-5.0 parts of modified asphalt; the 100 parts of mineral material I comprises 85-93 parts of coarse aggregate I, 3-11 parts of fine aggregate I and 3-5 parts of mineral powder I. The porosity of the asphalt concrete middle surface layer is 22.0-25.0%, and the implementation thickness of the asphalt concrete middle surface layer is 7.2-8.0 cm.
[0009] The filling gelling agent comprises the following raw materials in parts by weight: 100 parts of emulsified asphalt cement mortar, 0.03-0.06 parts of surfactant and 1.5-2.3 parts of accelerator; the 100 parts of emulsified asphalt cement mortar comprises 36-40 parts of modified emulsified asphalt, 56-60 parts of cement and 3-5 parts of water.
[0010] The modified asphalt wear layer comprises the following raw materials in parts by weight: 100 parts of mineral material II and 6.0-6.5 parts of high-viscosity modified asphalt; the 100 parts of mineral material II comprises 63-71 parts of coarse aggregate II, 23-31 parts of fine aggregate II and 5-7 parts of mineral powder II. The porosity of the modified asphalt wear layer is 3.0-5.0%; the thickness of the modified asphalt wear layer is 1.6-2.0 cm.
[0011] The asphalt concrete middle surface layer is mainly paved by mixture I. The grading type of mixture I is MOAC-16, specifically: the mass percentage of aggregate passing through the 19mm sieve size is 100%; the mass percentage passing through the 16mm sieve size is 90-100%; the mass percentage passing through the 13.2mm sieve size is 60-90%; the mass percentage passing through the 9.5mm sieve size is 40-60%; the mass percentage passing through the 4.75mm sieve size is 10-26%; the mass percentage passing through the 2.36mm sieve size is 9-20%; the mass percentage passing through the 1.18mm sieve size is 7-17%; the mass percentage passing through the 0.6mm sieve size is 6-14%; the mass percentage passing through the 0.3mm sieve size is 5-11%; the mass percentage passing through the 0.15mm sieve size is 4-9%; the mass percentage passing through the 0.075mm sieve size is 3-5%.
[0012] The mixing process of the mixture I is specifically as follows: heating the mineral material I to 180-190° C., adding the fiber and premixing for 15-20 seconds, then adding the modified asphalt heated to 165-175° C., mixing for 45-60 seconds, and obtaining the mixture I;
[0013] The raw materials of the mixture I are specifically as follows: the fiber is basalt fiber; the modified asphalt is SBS modified asphalt, preferably PG76-22 type SBS modified asphalt; the coarse aggregate I is basalt or alkaline diabase; the fine aggregate I is basalt rock chips; and the mineral powder I is basalt mineral powder.
[0014] The initial setting time of the filling gelling agent is 15 minutes, and the final setting time is within 45 minutes. The mixing process of the filling gelling agent is specifically as follows: in the process of stirring the modified emulsified asphalt, cement, surfactant and accelerator are sequentially added to the modified emulsified asphalt, stirred for 25 to 35 seconds, and then water is added and stirred for 2 to 4 minutes to obtain the filling gelling agent;
[0015] The raw materials of the filling gelling agent are specifically as follows: the modified emulsified asphalt is a medium-crack cationic modified emulsified asphalt with an evaporation residue mass content of more than 55%; the cement is ordinary Portland cement, preferably P.O42.5 ordinary Portland cement; the surfactant is a sodium rosin acid type air-entraining and water-reducing agent; the accelerator is an aluminothermic clinker type accelerator.
[0016] The modified asphalt wearing layer is mainly paved by mixture II, and the grading type of mixture II is UTFC-S, specifically: the mass percentage of aggregate passing through the 13.2mm sieve size is 100%; the mass percentage passing through the 9.5mm sieve size is 90-100%; the mass percentage passing through the 4.75mm sieve size is 37-43%; the mass percentage passing through the 2.36mm sieve size is 25-29%; the mass percentage passing through the 1.18mm sieve size is 18-23%; the mass percentage passing through the 0.6mm sieve size is 15-19%; the mass percentage passing through the 0.3mm sieve size is 10-16%; the mass percentage passing through the 0.15mm sieve size is 9-13%; the mass percentage passing through the 0.075mm sieve size is 7-10%.
[0017] The mixing process of the mixture II is specifically as follows: premixing the mineral material II for 15 seconds, then heating it to 180-190° C., then adding high-viscosity modified asphalt heated to 165-175° C., and mixing it for 45-60 seconds to obtain the mixture II.
[0018] The raw materials of the mixture II are specifically as follows: the high-viscosity modified asphalt is PG88-22 type high-viscosity modified asphalt; the coarse aggregate II is basalt; the fine aggregate II is basalt stone chips; and the mineral powder II is basalt mineral powder.
[0019] The modified emulsified asphalt tack coat is formed by spreading modified emulsified asphalt tack coat oil, and the modified emulsified asphalt tack coat oil is a medium-crack cationic modified emulsified asphalt with an evaporation residue mass content of more than 55%.
[0020] 2. A construction method for a composite anti-displacement asphalt concrete structure
[0021] The steps include:
[0022] S1) Use a milling machine to mill the original road surface implementation area;
[0023] S2) Mixing according to the proportion to obtain mixed material I and transporting it to the construction site;
[0024] S3) After the lower bearing layer is cleaned, the modified emulsified asphalt tack coat oil is evenly spread on the lower bearing layer to form a modified emulsified asphalt tack coat;
[0025] In the step S3), the amount of modified emulsified asphalt tack coat oil applied is 0.3-0.6 kg / m 2 ;
[0026] S4) After the modified emulsified asphalt tack coat oil is fully demulsified, the mixture I is spread on the modified emulsified asphalt tack coat using a paver;
[0027] In the step S4), the travel speed of the paver is controlled at 1-3 m / min, the discharge temperature of the mixture I is 170-185° C., and the paving temperature is not less than 160° C.;
[0028] S5) After the static pressing is completed, the asphalt concrete middle surface layer is formed;
[0029] During the static pressing process of step S5), the initial rolling temperature is 140-150°C, and the final rolling temperature is not less than 90°C.
[0030] S6) After the surface temperature drops below 80°C, use a pistol drill to drill a number of grouting holes on the surface of the asphalt concrete middle surface layer, clean the grouting holes, and then install the grouting nozzle;
[0031] S7) Mixing the filling gelling agent on site according to the proportion, and performing primary grouting and secondary grouting on the middle surface layer of the asphalt concrete in sequence;
[0032] In the step S7), 15 minutes after the mixing of the filling gelling agent is completed, the unused filling gelling agent is discarded;
[0033] During the initial grouting process: the installation depth of the grouting nozzle is 5-6 cm, a low-pressure pump is used for pumping, the grouting pressure is controlled at 2-3 MPa, and the grouting time of each grouting hole is controlled at 60-90 seconds;
[0034] During the secondary grouting process: the installation depth of the grouting nozzle is 2-3cm, and a low-pressure pump is used for pumping. The grouting pressure is controlled at 1-2Mpa. Each grouting is performed until the filling gelling agent within a radius of 3-3.5m around the grouting hole overflows and covers the road surface. When the grouting of each hole is completed, the next hole is grouted, and the gelling agent overflowing from the road surface is quickly cleaned up simultaneously, and the cleaned gelling agent is discarded;
[0035] S8) After the secondary grouting is completed, the road surface shall be cured for more than 6 hours, and vehicles are prohibited from entering during the curing period;
[0036] S9) After the curing is completed, the mixing plant mixes the mixture II according to the proportion and transports it to the construction site, and the mixture II is spread on the asphalt concrete middle surface layer using a paver;
[0037] In the step S9), the travel speed of the paver is controlled at 6-12 m / min, the discharge temperature of the mixture II is 170-185°C, and the paving temperature is not less than 160°C;
[0038] S10) After the static pressing is completed, a modified asphalt wear layer is formed;
[0039] During the static pressing process of step S10), the initial rolling temperature is 140-150°C, the final rolling temperature is not less than 90°C, and traffic is opened when the temperature drops to 50°C.
[0040] The composite anti-slip asphalt concrete structure and the construction method thereof provided by the invention are suitable for the treatment of rutting, slippage and other defects at national and provincial roads, municipal road intersections and long longitudinal slopes of highways of all grades.
[0041] The beneficial effects of the present invention are:
[0042] 1. The composite anti-displacement asphalt concrete structure provided by the present invention enables the formed pavement to have higher skeleton strength, early strength, water stability, good deformation resistance and rutting resistance, and at the same time has excellent road surface anti-skid performance and has higher application value.
[0043] 2. The construction method provided by the present invention forms an asphalt concrete middle surface layer with a porosity of more than 20% and a high-stability skeleton structure through paving, and then injects a filling gelling agent with good performance into the asphalt concrete middle surface layer to enhance the strength and the ability of the molded structure to resist displacement and deformation, so that the molded pavement structure has excellent shear resistance, compression resistance and flexural resistance. Then, by adding an ultra-thin modified asphalt wear layer, the anti-skid performance of the pavement is further enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a process principle diagram of the composite anti-displacement asphalt concrete structure of the present invention. DETAILED DESCRIPTION
[0045] To further illustrate the technical solution disclosed in the present invention, the present invention is further described below in conjunction with the accompanying drawings and specific implementation cases. The following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. All other embodiments obtained by those skilled in the art based on the embodiments of the present application without creative work are within the scope of protection of the present application.
[0046] The first aspect of the present invention provides a composite anti-displacement asphalt concrete structure. The composite anti-displacement asphalt concrete structure of the present invention comprises a modified emulsified asphalt adhesive layer, an asphalt concrete middle surface layer, a filling gelling agent and a modified asphalt wear layer. The asphalt concrete middle surface layer is spread on the surface of the modified emulsified asphalt adhesive layer, the filling gelling agent is formed inside the asphalt concrete middle surface layer by a grouting process, and the modified asphalt wear layer is formed on the surface of the asphalt concrete middle surface layer by a paving process.
[0047] Specifically, the modified emulsified asphalt tack coat is formed by spreading modified emulsified asphalt tack coat oil, and the modified emulsified asphalt tack coat oil is a medium-split cationic (+) modified emulsified asphalt with an evaporation residue mass content of more than 55%.
[0048] Specifically, the surface layer of asphalt concrete includes the following skeleton void components in parts by weight: 100 parts of mineral material I, 0.1-0.11 parts of fiber and 4.5-5.0 parts of modified asphalt; 100 parts of mineral material I include 85-93 parts of coarse aggregate I, 3-11 parts of fine aggregate I and 3-5 parts of mineral powder I.
[0049] Specifically, the filling gelling agent includes the following raw materials in parts by weight: 100 parts of emulsified asphalt cement mortar, 0.03-0.06 parts of surfactant and 1.5-2.3 parts of accelerator; 100 parts of emulsified asphalt cement mortar include 36-40 parts of modified emulsified asphalt, 56-60 parts of cement and 3-5 parts of water.
[0050] Specifically, the modified asphalt wearing layer includes the following skeleton dense components in parts by weight: 100 parts of mineral material II and 6.0-6.5 parts of high viscosity modified asphalt; 100 parts of mineral material II includes 63-71 parts of coarse aggregate II, 23-31 parts of fine aggregate II and 5-7 parts of mineral powder II.
[0051] Furthermore, the asphalt concrete middle surface layer has a high porosity. The porosity of the asphalt concrete middle surface layer is 22.0-25.0%, and the thickness of the asphalt concrete middle surface layer is preferably 8.0 cm.
[0052] Specifically, the asphalt concrete middle surface layer is mainly formed by paving mixture I.
[0053] Preferably, the gradation type of mixture I is MOAC-16. Specifically:
[0054]
[0055] Specifically, the mixing process of mixture I is as follows: heating mineral material I to 180-190°C, adding fibers and premixing for 15-20s, then adding modified asphalt heated to 165-175°C, mixing for 45-60s, and obtaining mixture I. As an optional embodiment of the present invention, the mixing process of mixture I is as follows: adding mineral material to a mixing pot and heating it to 180-190°C, then adding fibers into a mixing pot and premixing for 15-20s, then spraying modified asphalt heated to 165-175°C, mixing for 45-60s, and obtaining mixture I.
[0056] Preferably, in the asphalt concrete mid-surface layer:
[0057] The fiber is basalt fiber;
[0058] Coarse aggregate I is basalt or alkaline diabase;
[0059] Fine aggregate I is basalt rock chips;
[0060] Mineral powder I is basalt mineral powder;
[0061] The modified asphalt is SBS modified asphalt, preferably PG76-22 type SBS modified asphalt.
[0062] Among them, PG76-22 SBS modified asphalt includes the following technical indicators:
[0063] 1) 25℃, 100g, 5s, 0.1mm, needle penetration 50-70;
[0064] 2) The needle penetration index PI is not less than -0.2;
[0065] 3) Softening point T R&B Not less than 75℃;
[0066] 4) Dynamic viscosity at 135°C is not greater than 3.0 Pa·s;
[0067] 5) Elongation 5℃, 5cm / min, not more than 25cm;
[0068] 6) Flash point not less than 230℃;
[0069] 7) Solubility is not less than 99%;
[0070] 8) Elastic recovery at 25°C is not less than 75%;
[0071] 9) Storage stability separation, 48h softening point difference is not more than 2℃.
[0072] Therefore, the present invention uses basalt or alkaline diabase material with stable mechanical strength and adopts an open-graded structure to form an asphalt concrete middle surface layer with a porosity of 22.0-25.0% and a high-porosity skeleton void structure. During mixing, PG76-22 type SBS modified asphalt and basalt fiber are used to enhance the bonding strength and skeleton stability of the binder.
[0073] Furthermore, the initial setting time of the filling gelling agent is 15 minutes, and the final setting time is within 45 minutes.
[0074] Specifically, the mixing process of the filling gelling agent is as follows: in the process of stirring the modified emulsified asphalt, cement, surfactant and accelerator are sequentially added to the modified emulsified asphalt, stirred for 25 to 35 seconds, and then water is added and stirred for 2 to 4 minutes to obtain the filling gelling agent. As an optional embodiment of the present invention, the mixing process of the mixture II is as follows: start the mixer, put the modified emulsified asphalt into the mixer, and then sequentially put in cement, surfactant and accelerator, stir for 30 seconds, then add water and stir for 3 minutes to obtain the filling gelling agent.
[0075] Preferably, in the filler gelling agent:
[0076] The modified emulsified asphalt is a medium-split cationic (+) modified emulsified asphalt with an evaporation residue mass content of more than 55%;
[0077] The cement is ordinary Portland cement, preferably PO 42.5 ordinary Portland cement
[0078] The surfactant is a sodium rosin acid type air-entraining and water-reducing agent;
[0079] The accelerating setting agent is a thermite clinker accelerating setting agent.
[0080] Therefore, the present invention utilizes more than 20% of the interconnected voids in the high-porosity skeleton void structure and uses a high-performance filling gelling agent to fill the internal voids of the mixture I by grouting. The filling gelling agent uses medium-crack cation (+) modified emulsified asphalt as the base material: during the mixing process, the cation (+) in the modified emulsified asphalt reacts with the alkaline substances in the cement, so that the fine particles in the cement are quickly adsorbed on the modified emulsified asphalt, and then the filling gelling agent injected into the asphalt concrete reacts with the alkaline basalt or alkaline diabase stone material, and the fluidity is enhanced under the action of the surfactant, and it is quickly adsorbed around the stone; during the curing process, the cement in the filling gelling agent uses its water absorption and hydration heat to accelerate the demulsification speed of the emulsified asphalt, and enhance the adhesion and toughness of the formed pavement, and the water precipitated during the demulsification of the emulsified asphalt is absorbed by the cement and reacts with the hydroxy acid in the cement to increase the specific surface area, and quickly consolidates under the action of the accelerator, thereby enhancing the strength of the formed structure and its ability to resist displacement and deformation, so that the formed pavement structure has excellent shear, compression and flexural resistance.
[0081] Furthermore, the modified asphalt wear layer has high viscosity and meets the requirements of ultra-thin construction. The modified asphalt wear layer is used for the anti-skid performance of the road surface of the composite anti-slip asphalt concrete structure. The porosity of the modified asphalt wear layer is 3.0-5.0%; the thickness of the modified asphalt wear layer is preferably 2.0 cm.
[0082] Specifically, the modified asphalt wearing course is mainly formed by paving mixture II.
[0083] Preferably, the gradation type of mixture II is UTFC-S. Specifically:
[0084]
[0085] Specifically, the mixing process of mixture II is as follows: premixing mineral material II for 15 seconds, then heating it to 180-190°C, then adding high-viscosity modified asphalt heated to 165-175°C, and mixing it for 45-60 seconds to obtain mixture II. As an optional embodiment of the present invention, the mixing process of mixture II is as follows: premixing mineral material for 15 seconds after adding it to the mixing pot, then heating it to 180-190°C, then spraying high-viscosity modified asphalt heated to 165-175°C, and mixing it for 45-60 seconds to obtain mixture II.
[0086] Preferably, in the modified asphalt wearing layer:
[0087] Coarse aggregate II is basalt;
[0088] Fine aggregate II is basalt rock chips;
[0089] Mineral powder II is basalt mineral powder;
[0090] The high viscosity modified asphalt is PG88-22 type high viscosity modified asphalt.
[0091] Among them, PG88-22 high viscosity modified asphalt includes the following technical indicators:
[0092] 1) 25℃, 100g, 5s, 0.1mm, needle penetration not less than 50;
[0093] 2) Elongation 5℃, 5cm / min, not less than 40cm;
[0094] 3) Softening point T R&B Not less than 90℃;
[0095] 4) Dynamic viscosity at 135°C is not greater than 3.0 Pa·s;
[0096] 5) Dynamic viscosity at 60°C is not less than 100,000 Pa·s;
[0097] 6) Flash point not less than 230℃;
[0098] 7) Adhesive toughness is not less than 25N.m;
[0099] 8) Toughness not less than 20N.m;
[0100] 9) Solubility is not less than 99%;
[0101] 10) Elastic recovery at 25℃ is not less than 95%;
[0102] 11) Storage stability separation, 48h softening point difference is not more than 2.5℃.
[0103] Therefore, the present invention further enhances the anti-skid performance of the pavement of the composite anti-slip asphalt concrete structure by paving a modified asphalt wear layer with high viscosity and ultra-thin characteristics.
[0104] The second aspect of the present invention provides a construction method for the composite anti-movement asphalt concrete structure. Figure 1 The construction process flow and principle shown are used to introduce the construction method of the present invention in detail.
[0105] The construction method of the present invention comprises the following stages and steps:
[0106] Phase 1: Milling
[0107] S1) Use a milling machine to mill the original road surface implementation range, with a milling depth of 9.9 to 10.1 cm;
[0108] Stage 2: Evenly spread a layer of modified emulsified asphalt tack coat on the base after milling, and spread the asphalt concrete middle surface layer after demulsification;
[0109] S2) The mixing plant mixes the mixture according to the proportion to obtain the mixture I and transports it to the construction site;
[0110] S3) After the lower bearing layer is cleaned, the modified emulsified asphalt tack coat oil is evenly spread on the lower bearing layer using an emulsified asphalt spreading vehicle to form a modified emulsified asphalt tack coat;
[0111] Among them, the spreading amount of modified emulsified asphalt tack coat oil is 0.3~0.6kg / m 2 ;
[0112] S4) After the modified emulsified asphalt tack coat oil is fully demulsified, the mixture I is spread on the modified emulsified asphalt tack coat using a paver;
[0113] The travel speed of the paver is controlled at 1-3 m / min, the discharge temperature of the mixture I is 170-185°C, and the paving temperature is not less than 160°C;
[0114] S5) using a double steel wheel roller to perform static compaction 2 to 3 times, and forming an asphalt concrete middle surface layer on the surface of the modified emulsified asphalt adhesive layer after the static compaction is completed;
[0115] During the static pressing process, the initial rolling temperature is 140-150°C, and the final rolling temperature is not less than 90°C.
[0116] Stage 3: Initial grouting of the asphalt concrete middle surface layer;
[0117] Stage 4: After the initial grouting is completed, the secondary grouting is carried out in the order of the initial grouting until the gelling agent overflows and covers the road surface within 3m around the grouting hole, and then the overflowed gelling agent is quickly scraped off;
[0118] S6) After the surface temperature of the asphalt concrete middle surface layer drops below 80°C, a pistol drill is used to drill a number of grouting holes on the surface of the asphalt concrete middle surface layer. The spacing of the grouting holes is 5 to 6m, the distance between the grouting holes and the edge line of the implementation range is less than 3m, and the drilling depth of the grouting holes is 8 to 9cm. The grouting holes are cleaned with an air compressor, and then the grouting nozzles are installed;
[0119] S7) Mixing the filling gelling agent on site according to the proportion, and performing primary grouting and secondary grouting on the middle surface layer of the asphalt concrete in sequence; wherein the primary grouting and the secondary grouting are both performed from high to low and from inside to outside; the secondary grouting is performed in the order of the primary grouting;
[0120] It should be noted that the filling gelling agent must be grouted within 15 minutes after the mixing is completed. If the grouting is not completed within the time limit, the filling gelling agent should be deemed to be invalid and discarded to ensure the construction quality of the grouting material and the safety of the project. After the mixing is completed, the water precipitated from the demulsified modified asphalt reacts quickly with the cement, and the water absorption of the cement is used to accelerate the demulsification speed and increase the viscosity of the gelling agent. Under the action of the modified emulsified asphalt and the quick-setting agent, the cement quickly solidifies inside the mixture I, so that the mixture I is firmly bonded and the strength of the mixture I is improved. The gelling agent that has not been poured within 15 minutes must be discarded;
[0121] During the initial grouting process: the installation depth of the grouting nozzle is 6-7cm, a low-pressure pump is used for pumping, the grouting pressure is controlled at 2-3Mpa, and the grouting time of each grouting hole is controlled at 60-90S;
[0122] During the secondary grouting process: the installation depth of the grouting nozzle is 2 to 3 cm, and a low-pressure pump is used for pumping. The grouting pressure is controlled at 1 to 2 MPa. Each grouting is stopped when the gelling agent filling the road surface within 3 to 3.5 m around the grouting hole overflows and covers the road surface. When the grouting of each hole is completed, the next hole is grouting, and the gelling agent overflowing from the road surface is quickly cleaned up simultaneously and the cleaned gelling agent is discarded.
[0123] Phase 5: Health
[0124] S8) After the secondary grouting is completed, the road surface shall be cured for more than 6 hours, and vehicles are prohibited from entering during the curing period;
[0125] During the curing process, the cement in the filling gelling agent uses its own water absorption and hydration heat to accelerate the demulsification speed of the modified emulsified asphalt, thereby enhancing the adhesion and toughness of the formed pavement. The water precipitated during the demulsification of the modified emulsified asphalt is absorbed by the cement and reacts with the hydroxy acid in the cement to increase the specific surface area, and quickly solidifies under the action of the accelerator;
[0126] Stage 6: After curing, a layer of ultra-thin wear layer of high-viscosity modified asphalt is spread to enhance the anti-skid performance of the composite anti-slip asphalt concrete structure.
[0127] S9) After the curing is completed, the mixing plant mixes the mixture II according to the proportion and transports it to the construction site, and the mixture II is spread on the asphalt concrete middle surface layer using a paver;
[0128] The modified asphalt wear layer interlayer tack coat oil is the gelling agent remaining on the road surface in step S8), which softens under the high temperature of the hot mix II to form a tack coat;
[0129] The travel speed of the paver is controlled at 6-12 m / min, the discharge temperature of the mixture II is 170-185°C, and the paving temperature is not less than 160°C;
[0130] S10) using a double steel wheel roller to perform static pressing for 2 to 3 times, and after the static pressing is completed, a modified asphalt wearing layer is formed;
[0131] During the static compaction process, the initial compaction temperature is 140-150°C, the final compaction temperature is not less than 90°C, and traffic can be opened after the road surface temperature is lower than 50°C.
[0132] The specific embodiments of the present invention are as follows:
[0133] Unless otherwise specified, the following fractions are by weight.
[0134] Example 1
[0135] The composite anti-movement asphalt concrete structure provided in this embodiment includes a modified emulsified asphalt tack layer, an asphalt concrete middle surface layer, a filling gelling agent and a modified asphalt wear layer (upper surface layer).
[0136] The asphalt concrete middle surface layer contains 4.5 parts of modified asphalt, 0.1 parts of fiber and 100 parts of mineral material I, and the 100 parts of mineral material I include 85 parts of coarse aggregate I, 11 parts of fine aggregate I and 4 parts of mineral powder I.
[0137] The MOAC-16 gradation used in the mixture I of the asphalt concrete middle surface layer is as follows:
[0138]
[0139] The filling gelling agent comprises 0.06 parts of surfactant, 2.0 parts of accelerator and 100 parts of emulsified asphalt cement mortar, and the 100 parts of emulsified asphalt cement mortar include 40 parts of modified emulsified asphalt, 56 parts of cement and 4 parts of water.
[0140] The modified asphalt wearing layer contains 100 parts of mineral aggregate II and 6.0 parts of high-viscosity modified asphalt, and the 100 parts of mineral aggregate include 63 parts of coarse aggregate II, 30 parts of fine aggregate II and 7 parts of mineral powder II.
[0141] The UTFC-S type gradation used in the mixture II of the modified asphalt wearing course is as follows:
[0142]
[0143] Among them, the modified emulsified asphalt all adopts a certain brand of medium-crack cationic (+) modified emulsified asphalt with an evaporation residue content of more than 55%, the cement is a certain brand of PO 42.5 ordinary Portland cement purchased from outside, the surfactant is a certain brand of sodium rosin acid type air-entraining and water-reducing agent purchased from outside, and the accelerator is a certain brand of thermite clinker type accelerator purchased from outside.
[0144] The preparation method of the composite anti-slip asphalt concrete structure provided in this embodiment comprises the following steps:
[0145] D1) Mixture I for forming the middle surface layer of asphalt concrete is obtained by the following process: mineral material is added into a mixing pot and heated to 190°C, then the fiber is put into the mixing pot for premixing for 15 seconds, and then modified asphalt heated to 175°C is sprayed into it and mixed for 60 seconds to obtain mixture I for the middle surface layer of asphalt concrete.
[0146] D2) The filling gelling agent is obtained by the following process: start a mixer, put the modified emulsified asphalt into the mixer, then put cement, surfactant, and accelerator in sequence, stir for 30 seconds, then add water, stir for 3 minutes, and obtain the filling gelling agent.
[0147] D3) A mixture II for forming a modified asphalt wear layer is obtained by the following preparation method: the mineral material is added into a mixing pot and premixed for 15 seconds, and then heated to 180° C., and then high-viscosity modified asphalt heated to 175° C. is sprayed in and mixed for 60 seconds to obtain a modified asphalt wear layer mixture II.
[0148] The construction method of the composite anti-movement asphalt concrete structure provided in this embodiment comprises the following steps:
[0149] S1) Use a milling machine to mill the original road surface implementation area;
[0150] S2) The mixing plant mixes the mixture according to the proportion to obtain the mixture I and transports it to the construction site;
[0151] S3) After the lower bearing layer is cleaned, the modified emulsified asphalt tack coat oil is evenly spread on the lower bearing layer of the base using an emulsified asphalt spreading vehicle to form a modified emulsified asphalt tack coat;
[0152] Among them, the spreading amount of modified emulsified asphalt tack coat oil is 0.4kg / ㎡.
[0153] S4) After the modified emulsified asphalt tack coat oil is fully demulsified, the mixture I is spread on the modified emulsified asphalt tack coat using a paver;
[0154] Among them, the paver travel speed is 3m / min;
[0155] S5) using a double steel wheel roller to perform static compaction twice to form an asphalt concrete middle surface layer;
[0156] S6) After the surface temperature drops below 80°C, use a pistol drill to drill a number of grouting holes on the surface of the asphalt concrete middle surface layer. The spacing between the grouting holes is 6m, the distance between the grouting holes and the edge line of the implementation range is 3m, and the drilling depth of the grouting holes is 8cm;
[0157] Then use an air compressor to clean each grouting hole, and then install the grouting nozzle with a depth of 6cm;
[0158] S7) Mixing the filling gelling agent on site according to the proportion, and performing the initial grouting on the middle surface layer of the asphalt concrete in sequence. During the initial grouting process: the grouting is carried out from high to low and from inside to outside, and a low-pressure pump is used for pumping. The grouting pressure is controlled at 3Mpa, and the grouting time for each grouting hole is controlled at 1min;
[0159] After the first grouting is completed, the grouting holes are grouted for the second time in the order of the first grouting. The installation depth of the grouting nozzle is adjusted to 3cm, and the grouting pressure is controlled at 2Mpa. The grouting is stopped when the road surface gelling agent overflows and covers the road surface within 3m around the grouting hole, and the next hole is grouted. At the same time, the gelling agent overflowing from the road surface is quickly cleaned up and the cleaned gelling agent is discarded;
[0160] S8) After the secondary grouting is completed, the road surface shall be cured for more than 6 hours, and vehicles are prohibited from entering during the curing period;
[0161] S9) After the curing is completed, the mixing plant mixes the mixture II according to the proportion and transports it to the construction site, and the mixture II is spread on the asphalt concrete middle surface layer using a paver;
[0162] Among them, the paving speed is 10m / min;
[0163] S10) Use a double steel wheel roller to perform static compaction twice to form a modified asphalt wear layer, and open the road to traffic when the temperature drops to 50°C.
[0164] In this embodiment, the specific indicators of PG76-22 type SBS modified asphalt are:
[0165]
[0166] Residue after TFOT
[0167]
[0168] In this embodiment, the specific indicators of PG88-22 high viscosity modified asphalt are:
[0169]
[0170] Residue after TFOT
[0171]
[0172] Example 2
[0173] The composite anti-movement asphalt concrete structure provided in this embodiment includes a modified emulsified asphalt tack layer, an asphalt concrete middle surface layer, a filling gelling agent and a modified asphalt wear layer (upper surface layer).
[0174] The asphalt concrete middle surface layer contains 5.0 parts of modified asphalt, 0.1 parts of fiber and 100 parts of mineral material I, and the 100 parts of mineral material I include 92 parts of coarse aggregate I, 4 parts of fine aggregate I and 4 parts of mineral powder I.
[0175] The MOAC-16 gradation used in the mixture I of the asphalt concrete middle surface layer is as follows:
[0176]
[0177] The filling gelling agent comprises 0.04 parts of surfactant, 2.2 parts of accelerator and 100 parts of emulsified asphalt cement mortar, and 100 parts of emulsified asphalt cement mortar include 37 parts of modified emulsified asphalt, 58 parts of cement and 5 parts of water.
[0178] The modified asphalt wearing layer contains 100 parts of mineral aggregate II and 6.4 parts of high-viscosity modified asphalt, and the 100 parts of mineral aggregate include 70 parts of coarse aggregate II, 24 parts of fine aggregate II and 6 parts of mineral powder II.
[0179] The UTFC-S type gradation used in the mixture II of the modified asphalt wearing course is as follows:
[0180]
[0181] The modified emulsified asphalt, cement, surfactant and accelerator used in this embodiment are consistent with those in Example 1.
[0182] The preparation method of the composite anti-slip asphalt concrete structure provided in this embodiment comprises the following steps:
[0183] D1) Mixture I for forming the middle surface layer of asphalt concrete is obtained by the following process: mineral material is added into a mixing pot and heated to 185°C, then the fiber is put into the mixing pot for premixing for 20 seconds, and then modified asphalt heated to 170°C is sprayed into it and mixed for 50 seconds to obtain mixture I for the middle surface layer of asphalt concrete.
[0184] D2) The filling gelling agent is obtained by the following process: start a mixer, put the modified emulsified asphalt into the mixer, then put cement, surfactant, and accelerator in sequence, stir for 30 seconds, then add water, stir for 3 minutes, and obtain the filling gelling agent.
[0185] D3) A mixture II for forming a modified asphalt wear layer is obtained by the following preparation method: the mineral material is added into a mixing pot and premixed for 15 seconds, and then heated to 185°C, and then high-viscosity modified asphalt heated to 170°C is sprayed in and mixed for 50 seconds to obtain a modified asphalt wear layer mixture II.
[0186] The steps of the construction method of the composite anti-movement asphalt concrete structure provided in this embodiment are basically the same as those in Embodiment 1, except that:
[0187] In step S3), the amount of modified emulsified asphalt tack coat oil applied is 0.5 kg / ㎡;
[0188] In step S4), the paver travels at a speed of 2.5 m / min;
[0189] During the initial grouting process of step S7), the grouting pressure is controlled at 2 MPa;
[0190] In step S9), the paving speed is 8 m / min.
[0191] The specific indicators of PG76-22 SBS modified asphalt and PG88-22 high viscosity modified asphalt in this embodiment are the same as those in Example 1.
[0192] Example 3
[0193] The composite anti-movement asphalt concrete structure provided in this embodiment includes a modified emulsified asphalt tack layer, an asphalt concrete middle surface layer, a filling gelling agent and a modified asphalt wear layer (upper surface layer).
[0194] The asphalt concrete middle surface layer contains 4.7 parts of modified asphalt, 0.1 parts of fiber and 100 parts of mineral material I, and the 100 parts of mineral material I include 89 parts of coarse aggregate I, 7 parts of fine aggregate I and 4 parts of mineral powder I.
[0195] The MOAC-16 gradation used in the mixture I of the asphalt concrete middle surface layer is as follows:
[0196]
[0197] The filling gelling agent comprises 0.03 parts of surfactant, 2.3 parts of accelerator and 100 parts of emulsified asphalt cement mortar, and 100 parts of emulsified asphalt cement mortar include 36 parts of modified emulsified asphalt, 59 parts of cement and 5 parts of water.
[0198] The modified asphalt wearing layer contains 100 parts of mineral aggregate II and 6.3 parts of high-viscosity modified asphalt, and the 100 parts of mineral aggregate include 66 parts of coarse aggregate II, 27 parts of fine aggregate II and 7 parts of mineral powder II.
[0199] The UTFC-S type gradation used in the mixture II of the modified asphalt wearing course is as follows:
[0200]
[0201] The modified emulsified asphalt, cement, surfactant and accelerator used in this embodiment are consistent with those in Example 1.
[0202] The preparation method of the composite anti-slip asphalt concrete structure provided in this embodiment comprises the following steps:
[0203] D1) Mixture I for forming the asphalt concrete middle surface layer is obtained by the following process: mineral material is added into a mixing pot and heated to 180°C, then the fiber is put into the mixing pot for premixing for 20 seconds, and then modified asphalt heated to 165°C is sprayed into it and mixed for 50 seconds to obtain mixture I for the asphalt concrete middle surface layer.
[0204] D2) The filling gelling agent is obtained by the following process: start a mixer, put the modified emulsified asphalt into the mixer, then put cement, surfactant, and accelerator in sequence, stir for 30 seconds, then add water, stir for 3 minutes, and obtain the filling gelling agent.
[0205] D3) A mixture II for forming a modified asphalt wear layer is obtained by the following preparation method: the mineral material is added into a mixing pot and premixed for 15 seconds, and then heated to 180°C, and then high-viscosity modified asphalt heated to 175°C is sprayed in and mixed for 55 seconds to obtain a modified asphalt wear layer mixture II.
[0206] The steps of the construction method of the composite anti-movement asphalt concrete structure provided in this embodiment are basically the same as those in Embodiment 1, except that:
[0207] In step S3), the amount of modified emulsified asphalt tack coat oil applied is 0.6 kg / ㎡;
[0208] In step S4), the paver travels at a speed of 2.0 m / min;
[0209] In step S9), the paving speed is 6 m / min.
[0210] The specific indicators of PG76-22 SBS modified asphalt and PG88-22 high viscosity modified asphalt in this embodiment are the same as those in Example 1.
[0211] Comparative Example 1
[0212] The asphalt concrete structure of this comparative example includes a modified emulsified asphalt tack coat, an AC-20C asphalt concrete middle surface layer, and a modified AC-13C asphalt concrete upper surface layer. The materials used in each layer structure of this comparative example are as follows:
[0213] A. The modified emulsified asphalt adhesive layer adopts a certain brand of medium-cracked cationic (+) modified emulsified asphalt with an evaporation residue content of more than 55%;
[0214] B. The mixture of the AC-20C asphalt concrete middle surface layer is prepared with purchased 70# ordinary asphalt, and the gradation design is AC-20C, including 4.58 parts of 70# asphalt and 100 parts of mineral material. The 100 parts of mineral material include 64 parts of coarse aggregate, 30 parts of fine aggregate and 6 parts of filler; the designed porosity is 4.1%;
[0215] C. The mixture of the upper layer of modified AC-13C asphalt concrete is prepared with PG76-22 SBS modified asphalt, and the gradation design is modified AC-13C, including 4.84 parts of PG76-22 SBS modified asphalt and 100 parts of mineral material. The 100 parts of mineral material include 60 parts of coarse aggregate, 33 parts of fine aggregate and 7 parts of filler; the designed porosity is 4.2%.
[0216] The preparation method of the asphalt concrete structural raw material provided in this comparative example comprises the following steps:
[0217] D1) AC-20C asphalt mixture for forming the middle surface layer of AC-20C asphalt concrete is obtained by the following process: the mineral material is heated to 170°C, and then dry-mixed for 15 seconds, and then 70# ordinary asphalt heated to 160°C is sprayed into it and mixed for 50 seconds to obtain AC-20C asphalt mixture.
[0218] D3) A modified AC-13C asphalt mixture for forming the modified AC-13C asphalt concrete top layer is obtained by the following preparation method: the mineral material is heated to 185°C, and then dry-mixed for 15 seconds, and then PG76-22 type SBS modified asphalt heated to 175°C is sprayed into it and mixed for 60 seconds to obtain a modified AC-13C asphalt mixture.
[0219] The construction method of the asphalt concrete structure provided in this comparative example comprises the following steps:
[0220] S1) Use a milling machine to mill the original road surface within the implementation area, with a milling depth of 10 cm;
[0221] S2) The mixing plant mixes the AC-20C asphalt mixture according to the proportion and transports it to the construction site;
[0222] S3) After the lower bearing layer is cleaned, a layer of modified emulsified asphalt tack coat is first spread, with a spreading amount of 0.4kg / ㎡;
[0223] S4) After demulsification, the paving is performed using a paving machine with a paving thickness of 6 cm, a paving speed of 4 m / min, and a paving temperature of 140°C;
[0224] S5) After paving, a double steel wheel roller is used for initial rolling once, and a tire roller is used for re-rolling 6 times to obtain an AC-20C asphalt concrete middle surface layer;
[0225] S6) The mixing plant mixes the AC-13C modified asphalt mixture according to the proportion, and transports it to the construction site, where it is spread using a paver with a paving thickness of 4 cm, a paving speed of 3 m / min, and a paving temperature of 160°C;
[0226] S7) After paving, double steel wheel roller is used for initial rolling once, tire roller is used for re-rolling 5 times, and double steel wheel roller is used for final rolling once to obtain the modified AC-13C asphalt concrete top layer, and traffic is opened when the temperature drops to 50°C. In this comparative example, the specific indicators of PG76-22 SBS modified asphalt are:
[0227]
[0228] Residue after TFOT
[0229]
[0230] Comparative Example 2
[0231] This comparative example provides a SFP-13 macroporous infused modified asphalt concrete structure, including a modified emulsified asphalt adhesive layer, a macroporous modified asphalt concrete layer and an infused mortar. The materials used in the SFP-13 macroporous infused modified asphalt concrete structure provided in this comparative example are as follows:
[0232] A. The modified SFP-13 asphalt mixture of the large-pore modified asphalt concrete layer is prepared with PG88-22 high-viscosity modified asphalt, and the gradation design is SFP-13, including 3.0 parts of PG88-22 high-viscosity modified asphalt and 100 parts of mineral material, wherein the 100 parts of mineral material include 81 parts of coarse aggregate, 14 parts of fine aggregate and 5 parts of filler; the designed porosity is 30%.
[0233] B. The emulsified asphalt adhesive layer uses a certain brand of medium-crack cationic (+) modified emulsified asphalt with an evaporation residue content of more than 55%.
[0234] C. The pouring mortar adopts a certain brand of proprietary pouring mortar material, and the mass proportion of the mortar material is: 100 parts of dry powder and 32 parts of water.
[0235] The preparation method of the raw materials of the SFP-13 macroporous injection-type modified asphalt concrete structure provided in this comparative example comprises the following steps:
[0236] D1) The modified SFP-13 asphalt mixture is obtained by the following process: the aggregate is heated to 190°C and then dry-mixed for 15 seconds, and then PG88-22 type high-viscosity modified asphalt heated to 170°C is sprayed in and mixed for 50 seconds to obtain a modified SFP-13 modified macroporous mixture.
[0237] D2) Start the mixing tank first, then add water and dry powder of mortar material, then mix for 3 minutes, and then introduce the mixed materials into the finished product pot to obtain special mortar material.
[0238] The construction method of the asphalt concrete structure provided in this comparative example comprises the following steps:
[0239] S1) Use a milling machine to mill the original road surface within the implementation area, with a milling depth of 10 cm;
[0240] S2) The mixing plant mixes the modified SFP-13 asphalt mixture according to the proportion and transports it to the construction site;
[0241] S3) After the lower bearing layer is cleaned, a layer of modified emulsified asphalt tack coat oil is first spread, with a spreading amount of 0.5kg / ㎡;
[0242] S4) After demulsification, the paving is performed using a paving machine with a paving thickness of 10 cm, a paving speed of 2 m / min, and a paving temperature of 165°C;
[0243] S5) After paving, use a double steel wheel roller to statically press twice to form a large-pore modified asphalt concrete layer;
[0244] S6) When the road surface temperature drops below 40°C, grouting begins. The special mortar material is mixed on site according to the proportion, and the water pump is started to pump the mortar to the road surface. At the same time, the grouting personnel use a brush to flatten the excess mortar on the surface;
[0245] S7) After the grouting is completed, the mixture is cured for 5 hours to form an infused macroporous modified asphalt concrete layer (stress-bearing layer), thereby obtaining an SFP-13 macroporous infused modified asphalt concrete structure.
[0246] The specific indicators of the PG88-22 high-viscosity modified asphalt used in this comparative example are:
[0247]
[0248] Residue after TFOT
[0249]
[0250] The following shows the various performance preparations of the structures obtained in the examples and comparative examples of the present invention.
[0251] The performance indicators of the middle surface layer or stress layer mixtures of Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention are as follows:
[0252]
[0253] In the above table, the middle surface layer in Examples 1 to 3 refers to the middle surface layer of asphalt concrete after grouting and curing.
[0254] It can be seen from the above table that Examples 1 to 3 are superior to Comparative Example 1 in terms of rutting dynamic stability, immersion Marshall stability, residual strength of freeze-thaw splitting test, and residual Marshall stability, and are roughly equivalent to the performance of Comparative Example 2; but in terms of shear strength, Examples 1 to 3 are significantly superior to Comparative Example 1 and Comparative Example 2, proving that the composite anti-pushing asphalt concrete structure has a high promotion value in terms of the performance of the asphalt concrete mid-surface layer.
[0255] The performance indicators of the upper layer mixtures of Examples 1 to 3 and Comparative Example 1 of the present invention are as follows:
[0256]
[0257] It can be seen from the above table that Examples 1 to 3 are superior to Example 1 in terms of stability, rutting dynamic stability, Kentburg dispersion test loss, Schellenberg leakage loss, freeze-thaw splitting test residual strength, and residual Marshall stability, which proves that the composite anti-displacement asphalt concrete structure has a high promotion value in terms of the performance of the asphalt concrete top layer.
[0258] The results of the on-site detection tests of the road meter functions of Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention are as follows:
[0259]
[0260] It can be seen from the above table that Examples 1 to 3 are significantly better than Comparative Example 1 in terms of water permeability coefficient, and are similar to Comparative Example 2; they are significantly better than Comparative Examples 1 to 2 in terms of structural depth and friction coefficient, indicating that the present invention has very excellent anti-water permeability and anti-skid functions, can effectively extend the service life of the road surface, ensure driving safety, and has a high promotion prospect.
[0261] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, those skilled in the art should understand that any person skilled in the art can still modify the technical solutions described in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or perform equivalent replacements on some of the technical features thereof; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. They should all be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A composite anti-slip asphalt concrete structure, characterized in that: It includes a modified emulsified asphalt tack coat, an asphalt concrete middle surface layer, a filling gelling agent and a modified asphalt wear layer; the asphalt concrete middle surface layer is spread on the surface of the modified emulsified asphalt tack coat, the filling gelling agent is formed inside the asphalt concrete middle surface layer, and the modified asphalt wear layer is formed on the surface of the asphalt concrete middle surface layer; The asphalt concrete middle surface layer comprises the following raw materials in parts by weight: 100 parts of mineral material I, 0.1-0.11 parts of fiber and 4.5-5.0 parts of modified asphalt; the 100 parts of mineral material I comprises 85-93 parts of coarse aggregate I, 3-11 parts of fine aggregate I and 3-5 parts of mineral powder I; The filling gelling agent comprises the following raw materials in parts by weight: 100 parts of emulsified asphalt cement mortar, 0.03-0.06 parts of surfactant and 1.5-2.3 parts of accelerator; the 100 parts of emulsified asphalt cement mortar comprises 36-40 parts of modified emulsified asphalt, 56-60 parts of cement and 3-5 parts of water; The modified asphalt wear layer comprises the following raw materials in parts by weight: 100 parts of mineral material II and 6.0-6.5 parts of high-viscosity modified asphalt; the 100 parts of mineral material II comprises 63-71 parts of coarse aggregate II, 23-31 parts of fine aggregate II and 5-7 parts of mineral powder II.
2. The composite anti-displacement asphalt concrete structure according to claim 1, characterized in that: The porosity of the asphalt concrete middle surface layer is 22.0-25.0%, and the thickness of the asphalt concrete middle surface layer is 7.2-8.0 cm; The porosity of the modified asphalt wear layer is 3.0-5.0%; the thickness of the modified asphalt wear layer is 1.6-2.0 cm.
3. The composite anti-displacement asphalt concrete structure according to claim 1 is characterized by: The asphalt concrete middle surface layer is mainly paved by mixture I, and the gradation type of mixture I is MOAC-16, specifically: the mass percentage of aggregate passing through 19mm sieve size is 100%; the mass percentage passing through 16mm sieve size is 90-100%; the mass percentage passing through 13.2mm sieve size is 60-90%; the mass percentage passing through 9.5mm sieve size is 40-60%; the mass percentage passing through 4.75mm sieve size is 10-26%; the mass percentage passing through 2.36mm sieve size is 9-20%; the mass percentage passing through 1.18mm sieve size is 7-17%; the mass percentage passing through 0.6mm sieve size is 6-14%; the mass percentage passing through 0.3mm sieve size is 5-11%; the mass percentage passing through 0.15mm sieve size is 4-9%; the mass percentage passing through 0.075mm sieve size is 3-5%; The mixing process of the mixture I is specifically as follows: heating the mineral material I to 180-190° C., adding the fiber and premixing for 15-20 seconds, then adding the modified asphalt heated to 165-175° C., mixing for 45-60 seconds, and obtaining the mixture I; The fiber is basalt fiber; The modified asphalt is SBS modified asphalt; The coarse aggregate I is basalt or alkaline diabase; The fine aggregate I is basalt rock chips; The mineral powder I is basalt mineral powder.
4. The composite anti-displacement asphalt concrete structure according to claim 1 is characterized by: The initial setting time of the filling gelling agent is 15 minutes, and the final setting time is within 45 minutes; The mixing process of the filling gelling agent is specifically as follows: in the process of stirring the modified emulsified asphalt, cement, surfactant and accelerating agent are sequentially added to the modified emulsified asphalt, stirred for 25 to 35 seconds, and then water is added and stirred for 2 to 4 minutes to obtain the filling gelling agent; The modified emulsified asphalt is a medium-crack cationic modified emulsified asphalt with an evaporation residue mass content of more than 55%; The cement is ordinary Portland cement; The surfactant is a sodium rosin acid type air-entraining and water-reducing agent; The quick-setting agent is an aluminothermic clinker quick-setting agent.
5. The composite anti-displacement asphalt concrete structure according to claim 1, characterized in that: The modified asphalt wearing course is mainly paved by mixture II, and the gradation type of mixture II is UTFC-S, specifically: the mass percentage of aggregate passing through 13.2mm sieve size is 100%; the mass percentage passing through 9.5mm sieve size is 90-100%; the mass percentage passing through 4.75mm sieve size is 37-43%; the mass percentage passing through 2.36mm sieve size is 25-29%; the mass percentage passing through 1.18mm sieve size is 18-23%; the mass percentage passing through 0.6mm sieve size is 15-19%; the mass percentage passing through 0.3mm sieve size is 10-16%; the mass percentage passing through 0.15mm sieve size is 9-13%; the mass percentage passing through 0.075mm sieve size is 7-10%; The mixing process of the mixture II is specifically as follows: premixing the mineral material II for 15 seconds, heating it to 180-190° C., then adding high-viscosity modified asphalt heated to 165-175° C., and mixing it for 45-60 seconds to obtain the mixture II; The high-viscosity modified asphalt is PG88-22 type high-viscosity modified asphalt; The coarse aggregate II is basalt; The fine aggregate II is basalt rock chips; The mineral powder II is basalt mineral powder.
6. The composite anti-displacement asphalt concrete structure according to claim 1, characterized in that: The modified emulsified asphalt tack coat is formed by spreading modified emulsified asphalt tack coat oil, and the modified emulsified asphalt tack coat oil is a medium-crack cationic modified emulsified asphalt with an evaporation residue mass content of more than 55%.
7. A construction method for the composite anti-movement asphalt concrete structure according to any one of claims 1 to 6, characterized in that: The steps include: S1) Use a milling machine to mill the original road surface implementation area; S2) Mixing according to the proportion to obtain mixed material I and transporting it to the construction site; S3) After the lower bearing layer is cleaned, the modified emulsified asphalt tack coat oil is evenly spread on the lower bearing layer to form a modified emulsified asphalt tack coat; S4) After the modified emulsified asphalt tack coat oil is fully demulsified, the mixture I is spread on the modified emulsified asphalt tack coat using a paver; S5) After the static pressing is completed, the asphalt concrete middle surface layer is formed; S6) After the surface temperature drops below 80°C, several grouting holes are drilled on the surface of the asphalt concrete middle surface layer, the grouting holes are cleaned, and then the grouting nozzles are installed; S7) mixing the filling gelling agent on site according to the proportion, and performing primary grouting and secondary grouting on the middle surface layer of the asphalt concrete in sequence; S8) After the secondary grouting is completed, curing is performed for more than 6 hours; S9) After the curing is completed, the mixture II is mixed according to the proportion and transported to the construction site, and the mixture II is spread on the asphalt concrete middle surface layer using a paver; S10) After the static pressing is completed, a modified asphalt wear layer is formed.
8. The construction method of the composite anti-displacement asphalt concrete structure according to claim 7 is characterized by: In the step S3), the amount of modified emulsified asphalt tack coat oil applied is 0.3-0.6 kg / m 2 ; In the step S4), the travel speed of the paver is controlled at 1-3 m / min, the discharge temperature of the mixture I is 170-185° C., and the paving temperature is not less than 160° C.; During the static pressing process of step S5), the initial rolling temperature is 140-150°C, and the final rolling temperature is not less than 90°C.
9. The construction method of the composite anti-displacement asphalt concrete structure according to claim 7 is characterized by: In the step S7), 15 minutes after the mixing of the filling gelling agent is completed, the unused filling gelling agent is discarded; During the initial grouting process: the installation depth of the grouting nozzle is 5-6 cm, a low-pressure pump is used for pumping, the grouting pressure is controlled at 2-3 MPa, and the grouting time of each grouting hole is controlled at 60-90 seconds; During the secondary grouting process: the installation depth of the grouting nozzle is 2 to 3 cm, and a low-pressure pump is used for pumping. The grouting pressure is controlled at 1 to 2 MPa. Each grouting is done until the filling gelling agent within a radius of 3 to 3.5 m around the grouting hole overflows and covers the road surface.
10. The construction method of the composite anti-displacement asphalt concrete structure according to claim 7, characterized in that: In the step S9), the travel speed of the paver is controlled at 6-12 m / min, the discharge temperature of the mixture II is 170-185°C, and the paving temperature is not less than 160°C; During the static pressing process of step S10), the initial rolling temperature is 140-150°C, the final rolling temperature is not less than 90°C, and traffic is opened when the temperature drops to 50°C.